The Influence of Retail Awareness, Retail Association, Retail Perceived Quality, and Retail Loyalty on Purchase Intentions - Hanna Lula Latiefa; Drs. Anas Hidayat, MBA., Ph.D; Binarin Tirto Andika, S.E., M.Sc (Cita konsultindo, 2024)
This research aims to explain the influence of retail awareness, retail association, retail perceived quality, and retail loyalty on purchase intentions at Ami Mart retail in Magelang. Along with the rapid development of technology which influences people's lives in every way, especially the aspect of people's shopping life which has slowly changed dynamically, where most people are now interested in shopping in modern markets which are now found in every corner of Indonesia. In the current situation, modern markets are developing rapidly, especially in Indonesia. The sample used in this research was 115 respondents spread across Indonesia. The sampling technique uses convenience sampling. The analysis technique used is SEM analysis and processed with the AMOS version 24 application. The research results show that there is a positive and significant influence of retail awareness, retail association, retail perceived quality, and retail loyalty on purchase intentions. Keywo